2022
DOI: 10.1111/joca.12490
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in recollections of economic socialization, financial self‐efficacy, and financial literacy

Abstract: The OECD/INFE international surveys of adult financial literacy (OECD/INFE 2016, 2020) show gender differences in financial literacy in developed countries in Europe. In this study, we examine whether these differences can be explained by gender differences in parental economic socialization using the Dutch 2018 DHS household survey. We investigate whether respondents' recollection of economic socialization when young predict their adult economic behavior and self‐assessed financial knowledge. The results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…It was found that the students who received financial education and advice from their parents or guardians demonstrated higher levels of FSE (Vijaykumar, 2022). However, a study conducted by Furrebøe et al (2023) found that women have lower levels of FSE than men, despite similar levels of parental influence and guidance.…”
Section: (B) Social Contextmentioning
confidence: 96%
“…It was found that the students who received financial education and advice from their parents or guardians demonstrated higher levels of FSE (Vijaykumar, 2022). However, a study conducted by Furrebøe et al (2023) found that women have lower levels of FSE than men, despite similar levels of parental influence and guidance.…”
Section: (B) Social Contextmentioning
confidence: 96%
“…According to Furrebøe et al (2022), economic socialization in the family during childhood and adolescence is important for financial literacy and economic behavior in adulthood. They argue that there are relatively large gender differences in how financial knowledge and skills are obtained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both young and old women show low levels of financial literacy. Also, relatively large gender differences in financial literacy are even found in countries such as the Netherlands and Norway which are both relatively gender equal in terms of access to education and to the labor market (Furrebøe et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Literasi keuangan adalah selengkap intuisi, kemampuan, tindakan, sikap serta ilmu yang diperlukan demi membuat keputusan keuangan untuk tercapainya kesejahteraan keuangan seseorang (Furrebøe et al, 2022) Madura" sudah terbukti.…”
Section: Definisi Operasional Variable Penelitian 1 Literasi Keuanganunclassified